Protective and Social Motives behind Green Purchase Value: Evidence from Gen Z Green Cosmetics Consumers - Muhammad, Naufal Dzakwana; Saputro, Priangga Eko; Mala, Iva Khoiril; Asti, Arsy Annisa; Esera, Hilda (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2026)
Existing green marketing research largely conceptualizes Green Purchase Value (GPV) as the outcome of stable cognitive evaluations driven by environmental attitudes, social norms, and identity-based considerations. This approach overlooks how deeper, context-sensitive motivational systems may dynamically shape value construction, particularly in symbolic product categories such as cosmetics and within emerging markets. Addressing this theoretical gap, this study reconceptualizes GPV as a motivationally constructed outcome by integrating fundamental motives theory from evolutionary psychology into the sustainability marketing framework. Using a quantitative survey of 170 Generation Z consumers in Indonesia and analyzing the data with Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4, this study examines the effects of six fundamental motives, kin care, mate acquisition, mate retention, self-protection, group affiliation, and status seeking on GPV in the context of green cosmetics. The results reveal that group affiliation, mate acquisition, and self-protection exert significant positive effects on GPV, while kin care, mate retention, and status seeking do not. Theoretically, this study advances the GPV literature by demonstrating that value formation in green consumption is driven by adaptive social and protective motives rather than purely cognitive or identity-based evaluations. Practically, the findings suggest that green cosmetic brands should emphasize health protection narratives and community-based, lifestyle-oriented positioning to resonate with Generation Z consumers in emerging markets